(untitled) (Kairaranga, 2018)
The Incredible Years for Teachers programme (IYT) is an evidence-based classroom behaviour management programme which, since 2011, has been offered to teachers who are teaching students aged 3 - 8 years, in New Zealand primary schools and kindergartens. The IYT course has been designed so it can be flexibly implemented to meet the needs of course participants while still maintaining course fidelity. A critical component to individualising the IYT programme is between workshop and group leader teacher visits. This professional inquiry set out to identify how IYT group leaders, as part of teacher visits, can effectively support teachers to implement the IYT programme in their classes. Teachers’ perceptions of group leader actions that support them to implement the IYT programme in their classes were gathered using an online questionnaire. The main finding of this inquiry is a collaborative and differentiated approach based upon a coaching model should be utilised throughout all phases of the teacher visit. Findings from this inquiry suggest this could be best achieved through basing the group leader and teacher visit on the ‘Teaching as Inquiry’ cycle, as this is consistent with research about sustaining effective teacher learning.